Nitrogen uptake in fully organic, semi-organic and conventional rice fields in Madiun Regency. Issue 1 (1st April 2022) - Herdiansyah, Ganjar; Suntoro; Farid, Muhammad; Aziz, Mahafid; Dewi, Febridita sari; Slamet Rahayu, Adin
Abstract: Nitrogen is one of the essential nutrients for rice plants. However, the inappropriate use of nitrogen fertilizers can pollute the environment caused by the loss of N to groundwater and the atmosphere so that it can increase the nitrate content in the soil and greenhouse gas emissions. Therefore, optimal management of N nutrients is needed so that fertilization is in accordance with the needs of rice plants. This research aims to determine the estimation of nitrogen uptake in full organic, semi organic, and conventional rice fields. This research was conducted in Kab. Madiun, East Java. The research was conducted using qualitative, descriptive, and comparative methods as well as survey methods. Soil sampling used a stratified random sampling approach. Nitrogen uptake analysis was carried out by the Kjeldahl method. Data analysis was carried out by T-test. The results showed that the application of a fully organic system had a higher response than a semi organic system to plant biomass. The increase in plant biomass in full organic reached 20.36%, while semi-organic reached 2.91%. The highest tissue N content was in semi-organic. The application of semi-organic was able to increase the N uptake by 11.67% compared to the conventional system, while the full organic system was able to increase the N uptake by 1.87%.